The Manifestation of The Archetype Character Hafizhul Furqon in The Novel Di Antara Dua Sujud by Muhammad Irata: Literary Psychology - Amalia, Eka; Maulinda, Rerin (J-LELC: Journal of Language Education, Linguistics, and Culture, 2023)
This research examines the structure of Carl Gustav Jung’s analytic psychology theory. The object of the reseach is to looks how the archetypal structure of the main character Hafizhul Furqon in Muhammad Irata’s Novel “Di Antara Dua Sujud”. The purpose of this study is to determine what forms of archetypes explaining them clearly. This study uses a descriptive-qualitative method. The results of the study found that the main character dominated the Persona structure, portraying him as a selfless individual who suppresses his own feelings and prioritizes others. Additionally, in terms of the Self, Furqon is depicted as a simple person in his pursuit of happiness, taking full responsibility for his choices from the beginning and following through to the end. Finally, there exists the Shadow aspect; initially, Furqon elevates the status of women but undergoes a sudden change in attitude when he discovers a weakness in the woman her put on a pedestal, inducing him to hate her and shatter the hearts of women who had previously esteemed him